The roles of community nutrition scholars in changing mothers' child feeding, food preparation, and hygiene practices in southern Bangladesh - Kawarazuka, Nozomi; Ibrahim, F.; Rahaman, E.H.M.S.; Prain, Gordon (Frontiers Media, 2023)
Introduction: This qualitative study evaluates a nutrition and hygiene education program led by trained community nutrition scholars for 5,000 mothers of small children in the Khulna and Satkhira districts in southern Bangladesh. The objectives of this study are as follows: (1) understanding the processes and reasonings behind mothers’ improvement in child feeding, food preparation, hygiene, and homestead garden production, (2) understanding men’s roles in facilitating women’s behavioral changes, and (3) assessing the degree of changes in subjective notions of self-confidence, decision-making, and recognition among mothers and nutrition scholars. Methods: Data were collected through 14 focus group discussions with 80 participants and in-depth interviews with 6 women community nutrition scholars. Data was then analysed qualitatively by drawing on direct quotes from focus group discussions and interviews with detailed interpretation and account for respondents’ behaviors and perceptions. Results: Overall findings confirm behavior changes by women, their spouses, and other family members. Many women were able to independently decide to change food allocation and child feeding practices after gaining self-confidence through the training. Men performed vital roles, such as purchasing nutritious food in local markets, providing labor for land preparation of homestead gardens, and defending the women from the resistance to change by their mothers-in-law. Discussion: While the study supports the literature that women’s bargaining power in food/resource allocation is critical in child health and nutrition, the evaluation found that this process involves negotiations among family members. Engaging men and mothers-in-law in nutrition interventions have great potential to make nutrition interventions more eective.